Thickness‐Dependent Elastic Softening of Few‐Layer Free‐Standing MoSe2. Issue 23 (3rd May 2021) - Babacic, Visnja; Saleta Reig, David; Varghese, Sebin; Vasileiadis, Thomas; Coy, Emerson; Tielrooij, Klaas‐Jan; Graczykowski, Bartlomiej
Abstract: Few‐layer van der Waals (vdW) materials have been extensively investigated in terms of their exceptional electronic, optoelectronic, optical, and thermal properties. Simultaneously, a complete evaluation of their mechanical properties remains an undeniable challenge due to the small lateral sizes of samples and the limitations of experimental tools. In particular, there is no systematic experimental study providing unambiguous evidence on whether the reduction of vdW thickness down to few layers results in elastic softening or stiffening with respect to the bulk. In this work, micro‐Brillouin light scattering is employed to investigate the anisotropic elastic properties of single‐crystal free‐standing 2H‐MoSe2 as a function of thickness, down to three molecular layers. The so‐called elastic size effect, that is, significant and systematic elastic softening of the material with decreasing numbers of layers is reported. In addition, this approach allows for a complete mechanical examination of few‐layer membranes, that is, their elasticity, residual stress, and thickness, which can be easily extended to other vdW materials. The presented results shed new light on the ongoing debate on the elastic size‐effect and are relevant for performance and durability of implementation of vdW materials as resonators, optoelectronic, and thermoelectric devices. Abstract : The in‐plane elastic constants of a few‐layer suspended 2H‐MoSe2 soften about 30% while decreasing the thickness from bulk to three‐layers. The results obtained employing the contactless technique indicate the so‐called negative elastic size‐effect.